Faktor-Faktor Produksi yang Mempengaruhi Penerimaan Usahatani Bawang Merah pada Sistem Pengairan Pompa dan Tadah Hujan di Desa Songan A, Kecamatan Kintamani, Kabupaten Bangli - I DEWA GEDE AGUNG (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
The Production Factors that Affect the Income of Onion Farming with PumpSystem and Rainfed Sistern in the Village Songan A,Kintamani Sub District, Bangli RegencyBali has the potential for the development of commodity onion, especially in Banglidistrict listed as the biggest onion producer in Bali. Songan A village, KintamaniDistrict, Bangli deliberately chosen as the study area with the objective: Todetermine the most influencial production factors that affecting revenue magnitudefrom onion farmers between pump system and rainfed sistern.Onion farmers that has been chosen as much as 62 people consist as 30 farmers thatuse pump system and 32 farmers with rainfed, selected through proportionalrandom sampling. Data collected as qualitative data and quantitative data derivedfrom primary data and secondary data. Primary data collected by survey usingquestionnaires. Secondary data were obtained from the relevant government’s data.Data were analyzed using analysis functions reception and analyzed statisticallyusing multiple linear regression.The result shows: The production factors that affect the income of onion farmers atthe village Songan A. Based on function analysis of income, there is a differencebetween the pump system and rainfed onion farmers.The factors that greatly influence the income of onion farmers with the pumpsystem are other costs, depreciation rates of building and tools, and the seed cost.The factors that greatly influence the income of onion farmers in rainfed systems isdepreciation rates of buildings and tools, fertilizer cost, plants medicament, andother costs.